Folkloric Elements in the Internet Image of the Professional Basketball Player - Krikščiūnas, Povilas (Tautosakos darbai, 2017)
This article deals with folkloric and similar materials, namely, with texts and polycode pieces (consisting of both verbal and non-verbal elements) published on the Lithuanian web. The author focuses on certain more popular groups of typologically related texts / images or their combinations, and on the items particularly prone to variation. Demotivational posters and anecdotes are the most popular ones.Analysis of these materials reveals variations in content and form. Having grouped them, the author describes peculiarities and plausible origins of certain variants in separate sections. Mainly synchronic analysis is employed, but in cases of numerous facts revealing genesis of particular pieces, diachronic method is also applied.Unfortunately, only fans of the biggest Lithuanian basketball clubs (Žalgiris and Lietuvos rytas) and the national team are active enough to create an amount of material sufficient to analyze. The author is interested in aspects of team activities and personal features of the players that seem most notable for the internet users. These include relationships between teams, their attributes, personal and physical qualities of the players, professional level of the game, perception of teams as sports units, and style of the game. In case of international matches, the internet users associate players with national symbols or pieces of cultural heritage.Apparently, imperfect aspects of the game (both individual and as a team) are more popular, while moments of successful play receive less powerful expression. Internet users skillfully manipulate various elements of classical folklore borrowed from folktales, anecdotes, proverbs and proverbial sayings. For visual demotivational posters they most frequently use group pictures of the players or moments of the game. Graphically edited photos are also popular. The analyzed material is clearly a product of subcultural activity, since its creator is a community united by the same interest and using a special channel for communication. Peculiarities of creative paraphrases of this community depend on aspects of virtual and written, partly – of verbal folklore dissemination. This creativity not only enables basketball fans to perceive themselves as belonging to an integral socium, but also allows them to demonstrate their creative capacities, thus upgrading their own image.
Keywords: -